ALIRAN SEMPALAN DI KOTA BANJARMASIN (Kajian terhadap Ajaran Abah Pal Lima) - ARNI DAILY (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
The Sempalan sect taught by Abah Pal Lima has been developing for a long time, with a number of followers of more than seven thousand people scattered across different regions, and its teachings do not have a handbook. People are interested in this teaching because they have advantages such as alternative medicine and other magic powers. Throughout his teachings, he also believes in the presence of God, who has different qualities but does not believe in the foundations of faith and the pillars of Islam. So do not believe in the existence of gods, prophets, holy books (the Koran) as well as the question of taqdir, and there is no duty to worship and not to make prayers, fasting, zakat and pilgrimages. He assumed that besides him and his followers, they were considered heretics and would go to hell. This teaching gives priority to mental problems and believes that they are "inner people" who are in "culture" rather than "born" people in "the world." This is their reason for not carrying out the obligations ordered by Allah Almighty. The teachings of Abah Pal Lima is strongly influenced by the teachings of tasawuf wahdat al-wujud (unity of being) which was developed by Ibn Arabi, because it discusses the problem of Nur Muhammad and in humans, there is an element of divinity in addition to the element of being (al-Haq and al-Khalq). It is also influenced by the teachings of al-Farabi on the principle of emanation or delegation. The teaching of Abah Pal Lima was heretically rejected by the Banjarmasin City Ulema Council on 06 Jumadil Awwal 1439 A.D./23 January 2018 AD with a letter-number. 004/DPK-MUI / Bjm/1/1/2018, since the contents of the teachings, are in accordance with the ten criteria for heresy according to the MUI.